Distance learning during COVID-19 pandemic: A study of Moroccan university students - Habiba Hafa; Badr Hafa; Mohammed Moubtassime (International Journal of Evaluation and Research in Education (IJERE), 2023)
Because of COVID-19, distance learning was adopted by the majority of educational institutions as a strategy to ensure the continuity of education. In Morocco, forcing students to change their traditional learning methods has put them through an unprecedented learning experience. This study aims at investigating Moroccan university students of English experiences with distance learning during the pandemic in terms of readiness, satisfaction and perceived barriers. To achieve the objectives of the study, the researchers relied on an exploratory descriptive approach through a self-developed online questionnaire involving 138 respondents. The results indicate that students’ readiness to engage in distance learning was found to be at a moderate level. Additionally, the participants reported a low level of satisfaction with their experience of distance learning during COVID-19 pandemic. Thus, they preferred face-to-face learning over distance learning. Lack of previous experience with distance learning, lack of needed technology and inadequate internet connection were found to be among the major barriers to distance learning during the pandemic. Furthermore, the respondents expressed concerns on issues related to motivation, interaction and lack of technical skills. The findings of this study were discussed and compared to the findings of other related studies.